2019
DOI: 10.1038/s41598-019-52343-x
|View full text |Cite
|
Sign up to set email alerts
|

Vibration behavior of diamondene nano-ribbon passivated by hydrogen

Abstract: Diamondene is a new kind of two dimensional carbon allotrope with excellent properties and passivation approaches are often used to reduce the extremely high pressure required during its fabrication. When a one-end-clamped diamondene ribbon is hydrogenated on one surface, the ribbon tends to bend and vibrate due to asymmetric layout of C-H bonds on two surfaces. In the present work, the vibration behavior, including natural curvatures and vibration frequencies of diamondene ribbons, were investigated by molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This diamond-like nanoscale film formed by two-layer graphene upon compression exhibits stiffness and hardness comparable to diamond. Since then, diamond-like few-layer graphene sheets have attracted tremendous interest, because of their robust stability and excellent mechanical properties [11][12][13][14][15][16][17][18][19][20][21][22]. For example, Ke et al observed a semiconducting characteristic in compressed tri-layer graphene with an intrinsic band gap of around 2.5 eV [11].…”
Section: Introductionmentioning
confidence: 99%
“…This diamond-like nanoscale film formed by two-layer graphene upon compression exhibits stiffness and hardness comparable to diamond. Since then, diamond-like few-layer graphene sheets have attracted tremendous interest, because of their robust stability and excellent mechanical properties [11][12][13][14][15][16][17][18][19][20][21][22]. For example, Ke et al observed a semiconducting characteristic in compressed tri-layer graphene with an intrinsic band gap of around 2.5 eV [11].…”
Section: Introductionmentioning
confidence: 99%
“…By putting two or more graphene layers at high pressure, Martins et al [22] tested the phase transition that leading to diamondene [23][24][25][26][27]. The thermal and mechanical properties of diamondene were also explored for its wider engineering applications [28][29][30][31][32]. Jiang et al [33] proposed a new model of double-layered graphene that has a strain-dependent bandgap.…”
Section: Introductionmentioning
confidence: 99%
“…Low-dimensional carbon materials are classified into several groups, e.g., fullerene [ 1 , 2 ] as zero-dimensional material; a carbon nanotube (CNT) [ 3 ] as one-dimensional material; and two-dimensional materials containing graphene [ 4 , 5 ], graphane [ 6 , 7 , 8 ], diamondene [ 9 , 10 , 11 ]/diamane (with hydrogen atoms) [ 12 , 13 , 14 ], and diamond films [ 13 , 15 , 16 , 17 , 18 , 19 ]. Benefitting from the electron configurations, carbon materials have excellent properties in physics.…”
Section: Introductionmentioning
confidence: 99%